Humanizing the Localizing Sustainable Development Goals (SDGs) in Education and Research at Higher Education Institutions (HEIs) - Md Din, Mohd Fadhil; Omar, Wahid; Taib, Shazwin; Sarip, Shamsul; Krishnan, Santhana (Universitas Diponegoro, 2021)
Preliminary actions taken by the Universiti Teknologi Malaysia (UTM) towards the value-added from the Sustainable Development Goals (SDGs) framework that may relevant in the current indicators, elements, values and impacts, and the also constructive analysis by different sectors at High Educational Institutions (HEIs). Typically, the instrumentation on performances of each element (or indicator) in research and education portfolios are majorly defined as Key Performance Index (KPI) and/or Key Achievement/Amal Index (KAIs). All of instrumentations suitable at the vertical strategic plan to disseminate the workload across stakeholders in the HEIs. A strategic plan by each university will represent the core values and relevancy of niche area in academic and research sectors. However, UTM already is identifying the most critical element, far beyond the KPI/KAI successful story which focusses under the Pelan Global Universiti (PGU I-III) to outstanding values of inclusiveness, synergy and visibility with the important Desired State 2020. The UTM core values will serve Integrity, Synergy, Excellent and Sustainability (ISES) in all operation/services throughout trustworthy engagement with stakeholders. Meantime, the action plan for enVision 2025 institualized the pragmatic roadmaps align with the SDGs at the global benchmark, in order to horizontally manage the great grassroots improvement and further develop unique vision to UTM; named as UTMDNA. This paper describes the proactive strategic plan by UTM management to advocate the next roadmap altogether with high impact sustainable education and research works. Most of the concurrent achievement, action-plan and long-term Industrial Revolution 4.0 (IR 4.0) is emphasized in the life-balance strategy framework. The second wave (2020 - 2030) of SDGs in UTM is among the most recent thoughts towards the sustainability requirements specially to serve the UN SDG and enVision 2025 (UTM). Therefore, Malaysian higher education institutions should take proactive steps in culturing SDG initiatives – guided but not bounded by the specific measures set-out in the UN Conference